2022
DOI: 10.1016/j.heliyon.2022.e08829
|View full text |Cite
|
Sign up to set email alerts
|

Ethnozoological study of medicinal animals and animals’ products used by traditional medicinal practitioners and indigenous people in Motta city administration and Hulet Eju Enessie District, East Gojjam, Northwest Ethiopia

Abstract: Background: In Ethiopia, many ethnic communities use traditional/indigenous medicine for primary health care. However, this indigenous medicinal practice is being neglected and continued to be lost due to poor documentation as they are transferred from generation to generation through oral tradition. Therefore, this ethnozoological study aimed to assess and document the medicinal use of animals and animals' products used by traditional medicinal practitioners and indigenous people in Motta city administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
6
10
0
Order By: Relevance
“…The majority of participants were male (62.5% of the total), with 37.5% being female. Previous studies have reported a similar pattern in other parts of Ethiopia [ 7 , 20 ]. This is because, when aging, local doctors, specialists, and practitioners transfer their ethnomedicinal and magico-religious knowledge as an inheritance to their male sons or other close relatives.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The majority of participants were male (62.5% of the total), with 37.5% being female. Previous studies have reported a similar pattern in other parts of Ethiopia [ 7 , 20 ]. This is because, when aging, local doctors, specialists, and practitioners transfer their ethnomedicinal and magico-religious knowledge as an inheritance to their male sons or other close relatives.…”
Section: Discussionsupporting
confidence: 81%
“…Participants over the age of 55 made up a sizable proportion of the sample (94%) and were primarily involved in the use of ethnomedicine. Previous studies revealed a similar pattern in Ethiopia [ 7 , 20 ], demonstrating that older respondents had better expertise and understanding about ethnomedicine. There may be a variety of factors that increase knowledge with age; therefore, they should all be carefully considered.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations